The Effect of an Online Self-Help Cognitive Behavioural Intervention for Insomnia on Negative Affect and Paranoia: A Randomised Controlled Trial. (6th October 2020) - Scott, Alexander J.; Rowse, Georgina; Webb, Thomas L.
Background: Sleep and mental health go hand-in-hand, with problems sleeping being associated with a variety of mental health difficulties. Recently, insomnia has been linked with the experience of paranoia, a relationship that is likely to be mediated by negative affect. Given these links, the present research aimed to test whether a self-help intervention designed to improve sleep can also improve negative affect and paranoia. Method: Participants were recruited from a mailing list of University staff and were randomly allocated to one of three conditions; a wait-list control group, an active control group who completed a sleep diary each day for 6 weeks, and an experimental group who received an online self-help intervention targeting sleep problems alongside the same sleep diary. Levels of insomnia, negative affect, and paranoia were measured at baseline, immediately post-intervention, and 4- and 18-weeks post-intervention. Results: There were no significant differences between the groups on levels of insomnia, negative affect, and/or paranoid thinking at post-intervention, 4-weeks, or the 18-week follow-up. However, a relatively large number of participants dropped out of the study, particularly in the intervention group, which meant that the primary analysis was underpowered. Conclusion: Due to a high level of participant dropout, the findings from the present research are inconclusive, and suggest that retaining participants in trials of online interventions is a significant challenge that needs to be addressed in future research.